Are facial injuries really different? An observational cohort study comparing appearance concern and psychological distress in facial trauma and non-facial trauma patients. Issue 1 (January 2018) - Rahtz, Emmylou; Bhui, Kamaldeep; Hutchison, Iain; Korszun, Ania
Summary: Facial injuries are widely assumed to lead to stigma and significant psychosocial burden. Experimental studies of face perception support this idea, but there is very little empirical evidence to guide treatment. This study sought to address the gap. Data were collected from 193 patients admitted to hospital following facial or other trauma. Ninety (90) participants were successfully followed up 8 months later. Participants completed measures of appearance concern and psychological distress (post-traumatic stress symptoms (PTSS), depressive symptoms, anxiety symptoms). Participants were classified by site of injury (facial or non-facial injury). The overall levels of appearance concern were comparable to those of the general population, and there was no evidence of more appearance concern among people with facial injuries. Women and younger people were significantly more likely to experience appearance concern at baseline. Baseline and 8-month psychological distress, although common in the sample, did not differ according to the site of injury. Changes in appearance concern were, however, strongly associated with psychological distress at follow-up. We conclude that although appearance concern is severe among some people with facial injury, it is not especially different to those with non-facial injuries or the general public; changes in appearance concern, however, appear to correlate with psychological distress. We therefore suggest that interventions might focus on those with heightened appearance concern and should target cognitive bias and psychological distress.